2019
DOI: 10.31921/doxacom.n29a11
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms and bots applied to journalism. The case of Narrativa Inteligencia Artificial: structure, production and informative quality

Abstract: This research analyses the organization, work processes and quality of the information produced by Narrativa Inteligencia Artificial, the only company in Spain that writes journalistic texts using the software known as Gabriele for distribution to various media. The study was conducted over a six month period using in-depth, semi-structured interviews with four company professionals with complementary profiles, as well as participant observation during the process of creating an automated news item, and an onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 36 publications
0
7
0
10
Order By: Relevance
“…This old distinction can now have a new fashion regarding the production of news items produced exclusively or mainly by artificial intelligence systems or produced under the final responsibility of human authors, but the rights on the economic exploitation of all of them are, anyway, to be recognized to copyright holders of the collective work. Some scholars have examined these cases, and concluded that the common practice is for the corporate entities to sign those news items using the company's name, and scarcely mentioning the fact that they have been generated with artificial intelligence systems' aid [21] (p. 13).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This old distinction can now have a new fashion regarding the production of news items produced exclusively or mainly by artificial intelligence systems or produced under the final responsibility of human authors, but the rights on the economic exploitation of all of them are, anyway, to be recognized to copyright holders of the collective work. Some scholars have examined these cases, and concluded that the common practice is for the corporate entities to sign those news items using the company's name, and scarcely mentioning the fact that they have been generated with artificial intelligence systems' aid [21] (p. 13).…”
Section: Resultsmentioning
confidence: 99%
“…An individual approach to intellectual property (ultimately, an authors' rights approach) is more difficult to defend and the central role in copyright law is now that of the collective, and even of the derivative work. In the more optimistic views, this is good news for journalists, since artificial intelligence systems-aided production may free human journalists from heavy tasks and reserve them for an extra level of coverage [21] (p. 5,6) (reports and features, basically) with a more added value and, following the old Berne Convention literal, a more "literary" approach. Anyway, there are some ways to alternatively attribute authorship, or related rights, to a natural person or a corporate entity, and in every case AIS-aided news should be attribute to someone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The arguments for introducing robots on editorial offices have been many: greater accuracy (Silverman, 2013), increase of production (Papadimitriou, 2016), objectivity (Graefe, 2016), the ability to add web content (Mittal & Kumaraguru, 2014;Starbird et al, 2010), customising information (Hwang, Pearce & Nanis, 2012;Newman et al, 2019;Slater & Rouner, 2002;Young & Hermida, 2015), detecting events of journalistic interest for later diffusion (Steiner, 2014) and fighting against disinformation (Flew, 2012), especially in news and journalistic briefs (Ufarte & Manfredi, 2019), but also in Tweets and graphics (Rojas Torrijos & Toural, 2019). Likewise, they are used to identify the management of profiles on social networks (Chu et al, 2010;Dickerson, Kagan & Subrahmanian, 2014;Ferrara et al, 2016;Tavares & Faisal, 2013) and adapt to the preferences of users (Keeney, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…La IA se define como la implantación de mecanismos informáticos que efectúan, mediante algoritmos, tareas llevadas a cabo hasta entonces por humanos (Barrat, 2013). Su aplicación al periodismo tiene lugar gracias al trabajo de profesionales de la información, que nutren estos sistemas para generar informaciones automáticas a partir de una programación previa (Anderson, 2013;Ufarte Ruiz y Manfredi Sánchez, 2019).…”
Section: Introductionunclassified